How to pass the undergraduate obstetrics and gynaecology examination - Soe, Lwin; Tin, Moe Nwe; Muhammad, Shamsir; Awi, Idi (UNIMAS Publisher, 2012)
A books of questions is useful to students in many ways. It can be used to assess one's knowledge on what has been learned from textbooks, classrooms and bedside teaching. It is useful as revision tool. It also provides an avenue for an examination trial which in the case of multiple choice questions means to develop the skill to pick the right statements and not be tempte to guess answers. The answers which are given after each question serve as a quick guide to choice made. However students are reminded that this book is not textbook and cannot be treated as such. Reference given at teh end of the book indicates where students can refer to for a better understanding of the subject matter being tested.